RESPON JEPANG TERHADAP PERMINTAAN PEMBUKAAN LARANGAN IMPOR DAGING AYAM ASAL INDONESIA TAHUN 2018 - Muhammad Iqbal; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Japan imposed a ban on imports of chicken meat from Indonesia. The Japanese action was due to the fact that Indonesian chicken meat could not meet the standards set by Japan. The import ban on Indonesian chicken meat has been implemented by Japan since 2004. Indonesia is trying to re-export chicken meat to Japan by increasing the quality of domestic production. This study aims to explain the response given by Japan in responding to Indonesia's request to export chicken meat. This study uses an explanatory qualitative method with a mercantilist perspective and foreign policy theory. According to the mercantilist perspective, the state is an important actor in international trade. The economy is a tool to achieve the interests of the state. the active role of the state is very important in international trade. The theory used is the theory of international trade. By using this theory, we will find out how Japan is in the interest of the state in conducting trade with Indonesia. The results of this study concluded that Japan accepted Indonesia's request to reopen the import of chicken meat. However, Japan imposed conditions for chicken meat from Indonesia. First, Indonesia can only export processed chicken meat. Second, companies that will export have met the standards set by Japan. Third, Indonesia is opening beef imports from Japan. Keywords: chicken meat, import ban, trade restriction, mercantilism